2019
DOI: 10.1111/apa.14714
|View full text |Cite
|
Sign up to set email alerts
|

Active care of infants born between 22 and 26 weeks of gestation does not follow consensus expert recommendations

Abstract: Aim To determine the relationship between clinical practice and publication of an Australian consensus statement for management of extremely preterm infants in 2006. Methods A population‐based study using linked data from New South Wales, Australia for births between 22 + 0 and 26 + 6 weeks of gestation between 2000 and 2011. Results There were 4746 births of whom 2870 were liveborn and 1876 were stillborn. Of the live births, 2041 (71%) were resuscitated, 1914 (67%) were admitted into a neonatal intensive car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Overall, the outcome of preterm infants born in Australia has been maintained at a high level, as shown by Sinclair et al. . Once the resuscitation rate increased, this led to dramatic improvements in the survival rate.…”
Section: Future Directionsmentioning
confidence: 90%
See 2 more Smart Citations
“…Overall, the outcome of preterm infants born in Australia has been maintained at a high level, as shown by Sinclair et al. . Once the resuscitation rate increased, this led to dramatic improvements in the survival rate.…”
Section: Future Directionsmentioning
confidence: 90%
“…As Sinclair et al. stated in their paper, 99% of their subjects died if they did not receive any form of active resuscitation. Guidelines that state that resuscitation should not be started at a specific gestational age cannot be adapted in a timely manner, because the outcomes of these periviable preterm infants are rapidly changing.…”
Section: Active Initial Resuscitation Quick Withdrawal If Not Succeementioning
confidence: 91%
See 1 more Smart Citation
“…Most guidelines currently in use in Australia, include parental discretion around the resuscitation of babies below 24 or 25 weeks gestation [3,4,39]. Despite the negativity of clinicians and guidelines discouraging the resuscitation of babies under 24 weeks, many of these babies are receiving intensive care in Australia and a recent review of the use of the consensus guidelines in New South Wales and Australian Capital Territory reflect that resuscitation at 23 and even 22 weeks regularly occurs [40]. In North Queensland, nearly all babies at 24 weeks gestation and nearly half of babies delivered at 23 weeks gestation receive tertiary intensive care, regardless of place of delivery [10].…”
Section: Discussionmentioning
confidence: 99%
“…Sinclair et al. evaluated the relationship between the publication of an Australian expert consensus statement on resuscitating preterm infants born between 22 and 26 weeks of gestation and their short‐term outcomes. They found that the statement, which was published in 2006, was frequently not followed in clinical practice.…”
Section: Active Care Of Periviable Infants Did Not Follow Consensus Ementioning
confidence: 99%